If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -66x = 5x Combine like terms: 11x + -66x = -55x -55x = 5x Solving -55x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -55x + -5x = 5x + -5x Combine like terms: -55x + -5x = -60x -60x = 5x + -5x Combine like terms: 5x + -5x = 0 -60x = 0 Divide each side by '-60'. x = 0.0 Simplifying x = 0.0
| 5.1-7p=(-9.9) | | 3b+b+40= | | -3x+2.5=1.5(x+4) | | 3453253453452345235235325+456456464564646464+x=1 | | 2x^4+3x^3-11x^2-9x+15=0 | | x+1=77 | | -1.81=.5w+3.07 | | 3000c-900=3750 | | 6(x-4)+2x=8x+12 | | -18=15-3(6c+5) | | . 7x+1=2x+6 | | 6x+5=5x-10 | | x+8=3(x+2) | | 3(y+2)-2=16 | | ((5x+3-2)*27)*5=23-4 | | .34=(-1.53)-4h | | 7d-2d+6d-7-4d=0 | | ((5x+3-2)*27x)*5=23x-4 | | ((5y+3-2)*27y)*5=23x-4 | | 100+0.20x=70-0.50x | | -3(4+3x)=-9 | | 4x^2-8x+2=y | | 6x=1-(4-6x) | | 125-3x=42x+20 | | (5x-3y)*27x= | | log(3)+log(7)= | | 12-10x=86-24x | | 3w-6=4w-2 | | x=59+2500 | | 7-2z=-9 | | a=.5+28 | | 5(2Y-4)=2(5y-10) |